Audio engineering 101 a beginner's guide to music production - Dittmar, Tim (New York Routledge, 2018)
"Practical, concise, and approachable, Audio Engineering 101, Second Edition covers everything aspiring audio engineers need to know to make it in the recording industry, from the characteristics of sound to microphones, analog versus digital recording, EQ/compression, mixing, mastering, and career skills. Filled with hand-ons, step-by-step technique breakdowns and all-new interviews with active professionals, this updated edition includes instruction in using digital consoles, iPads for mixing, audio apps, plug-ins, home studios, and audio for podcasts. An extensive companion website features fifteen new video tutorials, audio clips, equipment lists, quizzes, and student exercises."--Provided by publisher.
Machine generated contents note: ch. 1 What Is Sound? Seven Important Characteristics -- ch. 2 How to Listen. Remember When Your Parents Told You to Listen? Well, You Should Have Listened! -- ch. 3 EQ Points of Interest. Frequencies Made Easy -- ch. 4 Mixing Consoles. So Many Knobs, So Little Time -- ch. 5 Signal Flow. The Keys to Directing Audio Traffic -- ch. 6 Microphone Guide and Their Uses. Hey, Is This Thing On? -- ch. 7 Signal Processors. Toys You Could Play With for Days! -- ch. 8 Studio Session Procedures. How a Recording Session Happens and in What Order -- ch. 9 Basic Acoustics. How to Make Your Recording Space Sound Better -- ch. 10 The History of Audio. It Helps to Know Where You Came From -- ch. 11 People Skills. Recording Isn't All Technical! -- ch. 12 Now That I Am Dangerous, Should I Get an Internship? -- ch. 13 Jobs. What Can I Do With These Skills? -- ch. 14 FAQs. Hear It From the Pros.
"A Focal Press book"--Cover.
Includes bibliographical references and index.
Keywords: Sound -- Recording and reproducing -- Handbooks, manuals, etc; Sound -- Recording and reproducing -- Digital techniques -- Handbooks, manuals, etc